Identification of the Genes Related to the Glycogen Metabolism in Hyperthermophilic Archaeon, Sulfolobus acidocaldarius - Lee, Areum; Bae, Eunji; Park, Jihee; Choi, Kyoung-Hwa; Cha, Jaeho (Frontiers in Microbiology, 2021)
Glycogen is a polysaccharide that comprises α-1,4-linked glucose backbone and α-1,6-linked glucose polymers at the branching points. It is widely found in organisms ranging from bacteria to eukaryotes. The physiological role of glycogen is not confined to being energy reservoir and carbon source but varies depending on organisms. Sulfolobus acidocaldarius, a thermoacidophilic archaeon, was observed to accumulate granular glycogen in the cell. However, the role of glycogen and genes that are responsible for glycogen metabolism in S. acidocaldarius has not identified clearly. The objective of this study is to identify the gene cluster, which is composed of enzymes that are predicted to be involved in the glycogen metabolism and confirm the role of each of these genes by constructing deletion mutants. This study also compares the glycogen content of mutant and MR31 strain and elucidates the role of glycogen in this archaeon. The glycogen content of S. acidocaldarius MR31, which is used as a parent strain for constructing the deletion mutant in this study, was increased in the early and middle exponential growth phases and decreased during the late exponential and stationary growth phases. The pattern of the accumulated glycogen was independent to the type of supplemented sugar. In the comparison of the glycogen content between the gene deletion mutant and MR31, glycogen synthase (GlgA) and α-amylase (AmyA) were shown to be responsible for the synthesis of glycogen, whereas glycogen debranching enzyme (GlgX) and glucoamylase (Gaa) appeared to affect the degradation of glycogen. The expressions of glgC–gaa–glgX and amyA–glgA were detected by the promoter assay. This result suggests that the gradual decrease of glycogen content in the late exponential and stationary phases occurs due to the increase in the gene expression of glgC–gaa–glgX. When the death rate in nutrient limited condition was compared among the wild type strain, the glycogen deficient strain and the strain with increased glycogen content, the death rate of the glycogen deficient strain was found to be higher than any other strain, thereby suggesting that the glycogen in S. acidocaldarius supports cell maintenance in harsh conditions.